Endogenous Biosynthesis of S-Nitrosoglutathione From Nitro-Fatty Acids in Plants - Mata-Pérez, Capilla; Padilla, María N.; Sánchez-Calvo, Beatriz; Begara-Morales, Juan C.; Valderrama, Raquel; Chaki, Mounira; Aranda-Caño, Lorena; Moreno-González, David; Molina-Díaz, Antonio; Barroso, Juan B. (Frontiers in Plant Science, 2020)
Nitro-fatty acids (NO2-FAs) are novel molecules resulting from the interaction of unsaturated fatty acids and nitric oxide (NO) or NO-related molecules. In plants, it has recently been described that NO2-FAs trigger an antioxidant and a defence response against stressful situations. Among the properties of NO2-FAs highlight the ability to release NO therefore modulating specific protein targets through post-translational modifications (NO-PTMs). Thus, based on the capacity of NO2-FAs to act as physiological NO donors and using high-accuracy mass-spectrometric approaches, herein we show that endogenous nitro-linolenic acid (NO2-Ln) can modulate S-nitrosoglutathione (GSNO) biosynthesis in Arabidopsis. The incubation of NO2-Ln with GSH was analysed by LC-MS/MS and the in vitro synthesis of GSNO was noted. The in vivo confirmation of this behaviour was carried out by incubating Arabidopsis plants with 15N-labelled NO2-Ln throughout the roots, and 15N-labelled GSNO (GS15NO) was detected in the leaves. With the aim to go in depth in the relation of NO2-FA and GSNO in plants, Arabidopsis alkenal reductase mutants (aer mutants) which modulates NO2-FAs levels were used. Our results constitute the first evidence of the modulation of a key NO biological reservoir in plants (GSNO) by these novel NO2-FAs, increasing knowledge about S-nitrosothiols and GSNO-signalling pathways in plants.